Клиническое наблюдение ложного острого живота на фоне тиреотоксического криза - S. N. Zavgorodniy; А. I. Rylov; М. B. Danylyuk; М. А. Kubrak (Клінічна хірургія)
Клиническое наблюдение ложного острого живота на фоне тиреотоксического криза